Накопичення аукубіну в листі видів роду Plantago L. флори України - Хортецька, Тая Володимирівна; Мазулін, Олександр Владиленович; Буряк, Валерій Прокопович; Єренко, Олена Костянтинівна; Мазулін, Георгій Владиленович; Chortecka, T. V.; Mazulin, O. V.; Burak, V. P.; Yerenko, O. K.; Mazulin, G. V. (My University, 2015)
Метою роботи було кількісне визначення аукубіну в листі досліджуваних видів роду Plantago L. і дослідження накопичення цієї сполуки під час цвітіння рослин в умовах України. Об’єктом дослідження була рослинна сировина (листя) P. major L., P. lanceolata L., P. media L. та P. altissima L., яку заготовлено в різних регіонах України (2010-2013 рр.) у період цвітіння. Ідентифікацію та визначення кількісного вмісту компонентів проводили за допомогою хромато-масспектрометрії. Встановлено присутність та кількісний вміст аукубіну в листі досліджуваних видів роду Plantago флори України. Методом газової хроматографії з мас-спектрометричним детектуванням вперше встановлено, що найвищі концентрації речовини характерні для листя P. altissima L. − до (2.57±0.13) %. Листя P. media L., P. altissima L., P. major L. перспективні для отримання протизапальних лікарських засобів. The aim of the work was quantitative determination of aucubin in the leaves of species of the genus Plantago L. and study of its accumulation during the flowering period in Ukraine. The objects of study were the leaves of P. major L., P. lanceolata L., P. media L. and P. altissima L., which were harvested in 2010-2013 in different regions of Ukraine during flowering. As a standard sample aucubin produced by «Fluka», Germany, was used. Identification and quantitative determination of components were performed by chromatography-mass-spectrometry. Analysis was conducted on chromatograph «Agilent Technology 6890N/5973N». The spectra of the components were compared to those in mass-spectral library database NIST02 (more than 174000 substances). It was found that aucubin during flowering accumulates in the leaves of all studied species of the genus Plantago from different habitat. The difference in aucubin concentrations in the investigated herbal drugs, depending on the year of harvesting and habitat was relatively low and ranged from (2.30±0.11) % to (2.57±0.13) %. For herbal drugs P. lanceolata L., P. major L. and P. media L., the results were respectively, from (0.77±0.04) % to (0.91±0.04) %; from (1.22±0.05) % to (1.37±0.07) % and from (1.55±0.07) % to (1.86±0.09) %. These results provide the need for standardization of herbal drugs of species of the genus Plantago. Leaves of Plantago L. is a valuable plant material to produce antimicrobial and anti-inflammatory drugs.
Aucubin accumulation in leaves of species of the genus Plantago L. of Ukrainian flora
Keywords: подорожник; аукубін; іридоїд; газова хроматографія з мас-спектрометричним детектуванням; гепатопротективна дія; антиоксидантна дія; plantago; aukubin; iridoids; gas chromatography with mass-spectrometry; gepatoprotective action; antioxidative action